Perception of Employers' in Transforming Technical and Vocational Education and Training vis-a-vis Emerging Technology Tools for Sustainable Workforce Development in Nigeria - Olabiyi, Oladiran Stephen; Chinedu, Caleb Chidozie (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2018)
Economic competitiveness of a country depends to a large extent on the skills of its workforce. The skills and the competencies of the workforce, in turn, are dependent upon the quality of the country’s education and training. Education and training are undergoing continuous change, and this change poses more challenges to the 21st-century workforce, and to training institutions. Despite the importance of TVET in transforming economic development, of any nation, Nigeria still has different perspectives about the competency of its TVET graduates. Therefore, the paper aims at determining the perceptions of Organized Private Sector (OPS) employers' regarding the competency of TVET graduates and the role of emerging technology tools in transforming TVET for a sustainable workforce development. Using a descriptive survey research design and a sample of 80 OPS employers. A validated and piloted questionnaire based on a 5-point Likert scale used as the data collection instrument for the study. Data were analysed using descriptive and inferential statistics including means, standard deviation and ANOVA. Data analysis was facilitated using the Statistical Package for Social Sciences (SPSS). Findings revealed that employers were not satisfied with the competency level of TVET graduates as it is showed that they are not well prepared to enter the competitive workforce and to be self-reliant. Given the nature and complexity of the field of TVET for a sustainable workforce, it was recommended that the utilization of adequate planning and management of emerging technology tools and resources in teaching TVET programs could contribute enormously to the quality and sustainability of the Nigerian workforce.